High Frequency Alternating Current (AC) Tangent Delta Measurement Technique for Underground Power Cable System - Ghani A.B.A.; Chakrabarty C.K.; Ramasamy A.K.; Avinash A.R.; Shafie H.; Permal N.; Danikas M.G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer software; Electric impedance measurement; Telecommunication cables; Testing; Underground cables; Distribution cables; Experimental values; High frequency alternating current; Higher frequencies; In-service failures; Insulation conditions; Measurement techniques; Underground power cable system; Cable sheathing